BLINATUMOMAB BRIDGING THERAPY FOR EFFECTIVE MANAGEMENT OF MRD IN PRO-B ALL WITH CNS INVOLVEMENT: A CASE REPORT OF POST TRANSPLANT PATIENT AT 23 MONTHS AFTER ALLOGENIC HEMATOPOIETIC CELL TRANSPLANTATION - Ceren Dehri Bahşi; Birol Güvenç (Hematology, Transfusion and Cell Therapy)
Objective: Pro-B ALL is an unusual and highly malignant form of ALL often presenting with CNS involvement. The involvement of the CNS makes the central objective of these treatments that is attaining and maintaining remission more challenging. This is a report of Pro-B ALL of a 52-year old female who had a CNS involvement and received blinatumomab both as bridge to allo -HSCT and post transplantation consolidation for MRD positivity.Case Report This 52 year old female is presented with Pro-B ALL. Standard chemotherapy was complicated by intracranial extension of the disease. The patient was positive for the Philadelphia chromosome with BCR-ABL (9;22) translocation hence dasatinib was added. Intrathecal therapy of blinatumomab was used as well due to infiltration of cytokines in the central nervous system. Following several sessions of treamtnet, complete remission including of central nervous system was achieved. Afterall the patient was to receive matche allo-HSCT post which clinical stabilization was ascertained.However bone marrow aspiration, biopsy and flow cytometry showed that there was persistence of MRD. However the patient had blinatumoma as targeted therapy. Discussion: This case illustrates the effective use of blinatumomab in managing Pro-B ALL with CNS involvement, particularly in the post-transplant setting. CNS involvement complicates treatment due to the blood-brain barrier, requiring targeted intrathecal therapy alongside systemic chemotherapy.Blinatumomab played a crucial role as a bridging therapy to allo-HSCT and in addressing MRD post-transplant, significantly reducing the risk of relapse. This case demonstrates that blinatumomab can effectively target MRD, even in patients with CNS involvement, contributing to better disease control and outcomes.